The effect of using Powtoon animated videos assisted by teacher explanation on seventh-grade students' vocabulary achievement - Davita Putri Agustina; Mutiara Bilqis; David Imamyartha (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Vocabulary is the foundation for developing language ability. Without extensive vocabulary knowledge, students frequently perform below their ability and may become discouraged from using languages. Animated videos like Powtoon can benefit learners by helping them enrich their vocabulary abilities. This study aims to determine whether using Powtoon animated videos assisted by teacher explanation significantly improves seventh-grade students’ vocabulary achievement in the classroom. The researchers used a quasi-experimental post-test-only design. The researchers used two classes with 29 students in an Islamic junior high school in this study. An analysis using the Mann-Whitney test exhibited a significant positive difference between the experimental and control classes. It was found that the use of Powtoon animated videos assisted by teacher explanation has a significant effect on seventh-grade students’ vocabulary achievement. Powtoon animated videos made it easier for teachers and students to teach and learn in the learning process.